INTERFERENSI KESALAHAN PENGUCAPAN FONEM BAHASA INDONESIA TERHADAP PENGUCAPAN FONEM BAHASA JERMAN YANG DILAFALKAN OLEH SISWA KELAS XII BAHASA DI SMA NEGERI 1 TARIK SIDOARJO - Syahputri, Abel Wahyu; Samsul, Suwarno Imam (LATERNE, 2022)
Language is an essential thing for human life. Language has a significant role in human life, namely as a means of communication. In learning a new language, there will be interference. Interference is a negative thing that occurs in the second language studied due to the first language, namely the mother tongue used by multilingual speech communities. Interference usually occurs in two languages that have similar language systems. Interference is regular when learning a new language. This study uses a corpus linguistic approach. The data used in this study comes from the students’ reading results in voice recordings. Then the data will be analyzed in the form of phoneme text in German. Furthermore, the text data will be categorized according to the location of the consonant errors, such as the beginning of the word, the middle of the word, and the end of the term. Then it will be matched between the transcription of student phonemes with Duden’s online dictionary. Most of the students who were the data sources in this study experienced interference errors in the consonants in the /sch/ sequence located at the beginning, middle, and end of the word.